DC serial arc fault recognition in aircraft using machine learning techniques - Raul Carreira Rufato; Thierry Ditchi; Cyril Van de Steen; Thierry Lebey; Yacine Oussar (International Journal of Electrical Power & Energy Systems)
Arc fault detection represents one of the major challenges for protection systems used in aeronautical industry due to the high demand in terms of reliability, robustness and detection time. Current aircraft has no system capable of recognize arc faults respecting those requirements. The problem becomes harder with the voltage levels increase expected in More Electric Aircraft (MEA) and for all electric or hybrid propulsion, pushing studies to consider more carefully the phenomenon of arc faults. This study proposes a machine learning approach to help detect DC serial arcs, which is a challenge in terms of recognition. The analysed database contains both current signal measurements of arc faults and nominal behaviours. A classifier is implemented based on the extraction of relevant features from the conventional current signals. The selection and design of the model is based on the Internal SVM – RFE technique. The obtained results demonstrate the best trade-off between all the performance requirements. The methodology is able to achieve a recognition rate of 98%.